ANALISIS PENERAPAN SISTEM PENGENDALIAN MANAJEMEN DENGAN MODEL FOUR LEVERS OF CONTROL PADA PT TASPEN (PERSERO) KANTOR CABANG MANADO - Siwu, Sweetly; Saerang, David; Tirayoh, Victorina (GOING CONCERN : JURNAL RISET AKUNTANSI, 2021)
Management Control System is a system used by a company to control the implementation of the planned strategy so that the company's goals can be achieved properly. Facing an increasingly competitive situation, a company needs a control system model that can ensure that the company's activities remain under control without preventing employees from innovating and being creative. The aim of this research is to know the implementation of management control system with four levers of control model at PT Taspen (Persero) Manado Branch Office. The research method used is descriptive qualitative method, while the data collection method is done through interviews, documentation and observation. The results of the study indicate that the implementation of the management control system has been running well because it has fulfilled the elements of the four levers of control.